New Insights on the Use of Polyphenols as Natural Preservatives and Their Emerging Safety Concerns - Ofosu, Fred Kwame; Daliri, Eric Banan-Mwine; Elahi, Fazle; Chelliah, Ramachandran; Lee, Byong-Hoon; Oh, Deog-Hwan (Frontiers in Sustainable Food Systems, 2020)
Polyphenols are natural high-valued secondary metabolites of plant that demonstrate strong antimicrobial potential as natural preservatives besides their well-established health promoting benefits. This review highlights the challenges, novel strategies to achieve industrial production of polyphenols and their safe use as potential alternative natural preservative. Since plant extraction presents considerable limitations of high cost due to excessive energy and solvent requirements, climate and long growth cycles, microbial biosynthesis using highly advanced omics techniques and metabolic engineering tools could provide superior alternative for commercial production of environmentally sustainable and cost-effective high-value metabolites in a short time. In spite of the many beneficial effects, some plant metabolites and polyphenol compounds at high dosage are found to be pro-oxidant or mutagenic with toxicity. Due to the controversial findings from sub-chronic and oral toxicity studies, more detailed safety and efficacy studies are needed to substantiate findings. Furthermore, extensive research efforts are required to ascertain optimal dosage for safe use in various foods to avoid potential harmful side effects.